The eco-travel guide : the worldwide way to go green...resorts, hotels, adventure - Fuad-Luke, Alastair, ....- (London : Thames & Hudson, 2008)
An essential resource for the next generation of travel: a liberating, responsible, and inspirational guide to resorts, hotels, cruises, and adventure. Travel habits today are changing: airlines are investing in greener fuels, carbon offset programs are gaining in popularity, and people increasingly are looking for alternative travel means and destinations.
Keywords: Duurzaam toerisme